Novos cerambycidae (coleoptera) da coleção Odette Morvan, Kaw, Guiana Francesa: III - Martins, Ubirajara R.; Galileo, Maria Helena M.; Tavakilian, Gérard L. (Papéis Avulsos de Zoologia, 2008)
New Cerambycidae (Coleoptera) of the Collection Odette Morvan, Kaw, French Guiana. New species described and figured of French Guiana: Oreodera mageia sp. nov. (Acanthoderini; Trestonia bilineata sp. nov. (Onciderini); Ischnolea odettae sp. nov. (Desmiphorini) and Icupima ampliata sp. nov. (Hemilophini). Plocaederus fragosoi (Cerambycini) is recorded for French Guiana.